Hepatitis Disease Diagnosis Expert System Using Certainty Factor: Hepatitis Disease Diagnosis Expert System Using Certainty Factor - Rabiatul Adawiyah Lubis; Fricles Ariwisanto Sianturi (Institute of Computer Science (IOCS), 2019)
This study discusses how to apply the method of Certainty Factor in the world of health, especially in diagnoas disease that resembles an expert and build intelligent systems sebauah based systems. The object of this study is hepatitis. various pemasalahan were encountered in the community such as lack of experts in the field of this disease and the high cost to the doctor. However, the issue of concern is the development of technology that has entered the digital age. This research resulted in an expert system which adopts the ability of an expert. The results of this study are expected to help the community in the diagnosis of hepatitis and soon overcome.